Proposal of a new surgical technique to repair gauge earlobe defect - Viviane Maria Maiolini; Lissiê Lunardi Sbroglio; Raphaella Barboza Marques; Roberta Teixeira da Silva; Marcella Leal Novello D’Elia (Surgical & Cosmetic Dermatology, 2020)
Earlobes deformities caused by adornments and ornaments are prevalent. The use of plugs and piercings in this topography generates a large partial cleft in the earlobes, which causes aesthetic and social damage when abandoning its use. The literature has already proposed several surgical techniques to correct defects in the earlobes. This case report describes a new, simple, and fast surgical approach, which had satisfactory aesthetic results in significant partial cleft cases: the adapted "L-plasty" technique.